Building information modeling for facilities management: A literature review and future research directions. (July 2019) - Matarneh, Sandra T.; Danso-Amoako, Mark; Al-Bizri, Salam; Gaterell, Mark; Matarneh, Rana
Abstract: Although a considerable number of studies on building information modeling (BIM) for facilities management (FM) have been conducted during the past ten years, a lack of consensus remains among academics and practitioners concerning the successful and practical information exchange process between BIM and FM systems. There is a need to establish an up-to-date synthesis on the current status of information exchange and interoperability between BIM and FM systems. After an in-depth review of 113 journal articles published from 2008 to 2018, this study systematically presents (1) a holistic review and critical reflection on the current status of BIM implementation in FM with a focus on information exchange and interoperability, (2) research trends and patterns and (3) research gaps and a future agenda in this area. Through a bibliometric and content review analysis, this paper concludes that the process of information exchange between BIM models and FM systems is not a straightforward process, as software interoperability remains a significant challenge. Bridging this gap requires standardized practical processes to integrate different information sources related to maintenance management, health & safety management tasks and BIM data, to provide a rich semantic database to support FM systems. Finally, it is hoped that this paper will advocate further developing a seamless information exchange process between BIM and FM systems to overcome interoperability issues and facilitate BIM implementation in FM. Graphical abstract: Image 1 Highlights: Information exchange between BIM models and FM systems is not a straightforward process, as software interoperability remains a significant challenge. Bridging this gap requires: ⁃ a seamless information exchange process between BIM and FM systems, ⁃ Holistic guidance for facility owners and managers that encapsulates all required information for efficient FM operations across all systems and building types, ⁃ a well-defined information quality process that ensures owner/FM needs are considered carefully in BIM models, ⁃ Standardized practical processes to integrate different information sources related to maintenance management and health & safety management tasks, to provide a rich semantic database to support FM systems, ⁃ a standardized process for feedback loops between operations and design phases to provide rich actual feedback to support efficient facilities design, and ⁃ More real-world case studies to investigate the current status of BIM implementation in FM.